Phytoavailability of Cd and Zn in soil estimated by stable isotope exchange and chemical extraction - Ayoub, Ahmed S.; McGaw, Brian A.; Shand, Charles A.; Midwood, Andrew J. (Plant and soil, 2003)
The distribution of labile Cd and Zn in two contrasting soils was investigated using isotopic exchange techniques and chemical extraction procedures. A sewage sludge amended soil from Great Billings (Northampton, UK) and an unamended soil of the Countesswells Association obtained locally (Aberdeen, UK) were used. 114Cd and 67Zn isotopes were added to a water suspension of each soil and the labile metal pool (E-value) determined from the isotope dilution. Samples were obtained at 13 time points from 1 h to 50 days. For the sewage sludge amended soil, 29 μg Cd g-1 (86% of total) and 806 μg Zn g-1 (65% of total) were labile and for the Countesswells soil the value was 8.6 μg Zn g-1 (13% of total); limits of detection prevented a Cd E-value from being measured in this soil. The size of the labile metal pool was also measured by growing plants for 90 days and determining the isotopic content of the plant tissue (L-value). Thlaspi caerulescens J. & C. Presl (alpine penny cress), a hyperaccumulator of Zn and Cd, Taraxacum officinale Weber (dandelion) and Hordeum vulgare L. (spring barley) were used. L-values were similar across species and lower than the E-values. On average the L-values were 23±0.8 μg Cd g-1 and 725±14 μg Zn g-1 for the Great Billings soil and 0.29±0.16 μg Cd g-1 and 7.3±0.3 μg Zn g-1 for the Countesswells soil. The extractable metal content of the soils was also quantified by extraction using 0.1 M NaNO3, 0.01 M CaCl2, 0.5 M NaOH, 0.43 M CH3COOH and 0.05 M EDTA at pH 7.0. Between 1.3 and 68% of the total Cd and between 1 and 50% of the total Zn in the Great Billings soil was extracted by these chemicals. For the Countesswells soil, between 6 and 83% of the total Cd and between 0.1 and 7% of the total Zn was extracted. 0.05 M EDTA and 0.43 M CH3COOH yielded the greatest concentrations for both soils but these were less than the isotopic estimates. On the whole, E-values were numerically closer to the L-values than the chemical extraction values. The use of isotopic exchange provides an alternative estimate of the labile metal pool within soils compared to existing chemical extraction procedures. No evidence was obtained that T. caerulescens is able to access metal within the soil not freely available to the other plants species. This has implications for long term remediation strategies using hyperaccumulating plant species, which are unlikely to have any impact on non-labile Cd and Zn in contaminated soil.